Application of Discrete Event Simulation in Estimating Productivity of Shotcrete Method in Divider Wall Construction - Plamenco, Dean Ashton; Germar, Fernando; Caparros, Paolo (International Journal of Sustainable Construction Engineering and Technology, 2021)
Discrete-event simulation (DES) techniques are widely used in modeling complex environments where interaction between time-dependent resources and system processes occur in sequences, such as manufacturing ecosystems or production lifecycles, providing an alternative to traditional work measurement. In this study, labor productivity of using shotcrete process in constructing wall dividers for a simple construction project is estimated using a discrete-event simulation (DES) software incorporating project data on process durations, setup time, and machine mean time to failure (MTTF) as model inputs. The simulated productivity rate of using shotcrete to construct a 1000-sq.m. wall in replications of 200, 500, and 1000 is 1.59 man-hours/sq.m., compared to computed rate of 1.33 man-hours/sq.m. using the Program Evaluation and Review Technique (PERT). The total waiting time with respect to the simulation time considering setup, process-in-waiting, and downtime is 48.9% for a single 8-hour shift per workday arrangement. It is shown that by doing multiple 8-hour shifts the resource utilization of the shotcrete equipment can be improved by an average of 43.8% per additional shift bringing the total waiting time to 9.21% for a continuous 8-hour shifts in a single workday. The methodology aims to provide a better baseline estimate of productivity as it takes in to account historical data as well as waiting time arising from resource limitations.